Power, politics and maritime governance in the Indian Ocean - Schöttli, Jivanta (Routledge, 2015)
Power, politics and maritime governance in the Indian Ocean / Jivanta Schöttli -- The Indian Ocean Rim - Association for Regional Co-operation (IOR-ARC): the futile quest for regionalism? / Christian Wagner -- The Indian Ocean Region in India's strategic futures: looking out to 2030 / Krishnappa Venkatshamy -- The reluctant pretender: China's evolving presence in the Indian Ocean / Jonathan Holslag -- The French strategic vision of the Indian Ocean / Isabelle Saint-Mézard -- European (British and French) geostrategy in the Indo-Pacific / James Rogers -- The US Navy's Indo-Pacific challenge / Toshi Yoshihara -- Piracy and maritime governance in the Indian Ocean / Peter Lehr.